Faktor - Faktor yang Mempengaruhi Kinerja Pegawai pada Pia “Wijaya” - Naluri Nafi’ Annurudzati; Nersiwad Nersiwad; Budi Utami (Universitas Katolik Widya Karya Malang, 2023)
Companies with high performance can plan various policies. Performance is the result of work in quality and quantity achieved by a person in carrying out their duties in accordance with the responsibilities given to them. Humans as the wanting creature means that humans naturally have various desires and needs that will never run out. It is with this aim to fulfill the desires and needs that humans work. The purpose of this research is to find out whether motivation has a partial effect on employee performance at Pia Wijaya, to find out whether the work environment has a partial effect on employee performance at Pia Wijaya, to find out whether salary has a partial effect on employee performance at Pia Wijaya, to find out whether work discipline has a partial effect on employee performance at Pia Wijaya, to find out whether job satisfaction has a partial effect on employee performance at Pia Wijaya and to find out whether motivation, work environment, salary, work discipline, and job satisfaction have a simultaneous effect on employee performance . In this study, researchers used a type of quantitative research. The quantitative approach is an approach in research that uses numbers to analyze the relationship between variables (Sugiyono, 2014). The results in this study are that the significance value of X1 is 0.199 > 0.05, which means that X1 does not affect Y or motivation does not affect employee performance at PIA WIJAYA, the significance value of X2 is 0.530 > 0.05, which means that X2 does not affect Y or work environment has no effect on employee performance, the significance value of X3 is 0.793 > 0.05, which means that X3 has no effect on Y or salary has no effect on employee performance, the significance value of X4 is 0.275 > 0.05, which means that work discipline X4 has no effect on Y or work discipline has no effect on employee performance. The effect of job satisfaction on employee Y performance, the significance value of X5 is 0.914 > 0.05, which means that X5 has no effect on Y or job satisfaction has no effect on employee performance, a significance result of 0.735 which is greater than 0.05. Thus it can be concluded that there is no simultaneous influence of X1, X2, X3, X4 AND X5 on Y.